Search for the minimum thermal conductivity in mixed cryocrystals (CH4)1-x Krx: Статьи, посвященные столетию со дня рождения Л. В. Шубникова - Konstantinov, V. A.; Manzhelii, V. G.; Revyakin, V. P.; Pohl, R. O. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
The isochoric thermal conductivity of (CH4)1-x Krx solid solutions is studied between 40 K and ~ 150 K over the wide range of concentrations (x = 0.013, 0.032, 0.07, 0.115, 0.34, 0.71, 0.855, 0.937, and 0.97). A gradual transition from the thermal conductivity of a highly perfect crystal to the minimumthermal conductivity is observed as the crystal becomes increasingly more disordered. A qualitative description is given in the framework of Debye model of thermal conductivity, which takes into consideration the fact that phonon mean free path cannot decrease indefinitely.